Respuesta :

qabtt

First, we are going to want to plug in the values we are given. In this case, we will end up with the equation:

[tex]6 = (4 - c) 2[/tex]


From here, we can solve the equation to find [tex]c[/tex]:

[tex]6 = 2(4 - c)[/tex]

  • Apply the commutative property to rearrange the terms on the right-side of the equation to make the distributive property more apparent

[tex]6 = 8 -2c[/tex]

  • Apply the distributive property

[tex]-2 = -2c[/tex]

  • Subtract 8 from both sides of the equation

[tex]1 = c[/tex]

  • Divide both sides of the equation by -2

We have found that c = 1.